Vitamin B supplementation enhances the efficacy of non-steroidal anti-inflammatory drugs in patients with painful foot and ankle conditions: A multicenter, prospective, randomized controlled trial - Myung-Geun Song; Chul Hyun Park; Young-Rak Choi; Gi-Won Choi; Bom Soo Kim (PLoS ONE, 2025)
Objective The management of foot disorders often involves anti-inflammatory drugs for chronic inflammation and pain. Combining anti-inflammatory drugs with vitamin B complex may have a synergistic effect, but its efficacy in foot disorders remains unclear. This study aimed to investigate the effects of combining vitamin B complex with anti-inflammatory drugs in patients with foot disorders. Methods This study enrolled 201 patients aged ≥ 19 years with foot disorders of Achilles tendinitis, foot or ankle arthritis, Civinini-Morton syndrome (Morton’s neuroma), or plantar fasciitis from four hospitals in Korea between October 2020 and December 2021. The patients were randomized in a 1:1 ratio to receive either aceclofenac 100 mg twice daily alone (control group, n = 77) or aceclofenac 100 mg and vitamin B complex twice daily (experimental group, n = 79) for 4 weeks. Among 201 randomized participants, 156 patients(79 in the experimental group and 77 in the control group) completed all scheduled follow-up visits and were included in the final analysis. The primary outcome measure was pain as assessed using the 10-cm visual analog scale (VAS). The secondary outcome measures were health-related quality of life and foot/ankle outcomes as assessed using the EuroQol 5 Dimension (EQ-5D) questionnaire and the Foot and Ankle Outcome Score (FAOS), respectively. Results VAS scores were more significantly reduced in the experimental group than in the control group, after 4 weeks (−2.87 ± 1.86 (from 6.95 ± 0.15 to 4.08 ± 0.17) vs. −0.91 ± 1.81 (from 5.99 ± 0.14 to 5.08 ± 0.21], p < 0.001). Similarly, improvements in the EQ-5D scores were significantly greater in the experimental group (0.079 ± 0.143 (from 0.69 ± 0.01 to 0.77 ± 0.01] vs 0.008 ± 0.111 (from 0.75 ± 0.01 to 0.76 ± 0.01], p = 0.001). Additionally, the increase in FAOS after treatment was significantly larger in the experimental group (9.94 ± 14.38 vs 2.97 ± 11.79, p = 0.001). Subgroup analysis revealed the combined therapy was particularly more effective in patients with chronic symptoms lasting over 3 months and in conditions like plantar fasciitis, foot or ankle arthritis, and Civinini-Morton syndrome. Conclusion Combining vitamin B complex with anti-inflammatory drugs effectively reduces pain and improves function in patients with chronic foot disorders. This combination therapy offers a promising strategy for improving pain control and functional outcomes in orthopaedic outpatient settings. Trial registration This study was registered at Clinical Research Information Service, Korea Centers for Disease Control and Prevention, Ministry of Health and WELFARE (Republic of Korea, https://cris.nih.go.kr/cris/search/detailSearchEn.do?seq=27976 ), a WHO International Clinical Trials Registry Platform primary register setup, on May 19,2020 under the registration number KCT0005035.